Dispersion corrected interaction of polar and nonpolar fluids confined within carbon nanotubes: Density functional theoretical analysis using Grimme's D3 scheme. Issue 14 (23rd December 2017) - Sahu, Pooja; Ali, Sk. Musharaf
Abstract: The structural and flow characteristics of fluids within carbon nanotube (CNT) is dictated by the interaction of fluid molecules within the nanocavity of CNT. Therefore, in the present study, dispersion corrected density functional theory has been used to investigate the structure and interaction of polar and nonpolar molecules within CNT. The present study shows that there is profound effect on the interaction due to dispersion. The interaction energy of the confined water was found to be reduced with increasing distance of the water molecule from the wall of the CNT. The water is preferentially adsorbed over methane due to stronger interaction with CNT over methane. Further, water is preferentially adsorbed over methanol molecule when interaction is calculated without dispersion but after inclusion of dispersion interaction, the calculated results show that the methanol–CNT interaction is stronger than that of water molecule and hence preferentially adsorbed within the CNT as revealed from MD simulation. The present calculation reveals that that the effect of CNT confinement on the IR spectra of the single file water is quite considerable compared to the IR spectra of tetrahedral bulk water cluster. Therefore, the present results might be useful for the separation of polar molecule from nonpolar molecule during fabrication of CNT‐based filter and purification system. Abstract : The structural and flow characteristics of fluids inside carbon nanotube (CNT) is dictated by the interaction of fluid molecules within the nanocavity. Properly accounting for dispersion interactions is of paramount importance to model such systems. Dispersion interactions strongly affects how the components of water–methane mixtures adsorb on the CNT walls, informing the design of CNT‐based filter and purification systems for the separation of polar and nonpolar fluids.